Kontekstualisasi Filsafat Politik al-FÃ¢rÃ¢bÃ® dalam Pemikiran Politik Modern - Muthhar, Moh. AsyÃ¢Â€Â™ari (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The article describes that in light of al-MadÃ®nah al-FÃ¢á¸ilah, al-FÃ¢rÃ¢bÃ® idealized the relationship between state and its citizens based on ethical values. This is in order to create a society who recognize the truth and enforce it in the form of cooperation with the state to build mutual prosperity. According to al-FÃ¢rÃ¢bÃ®, society is a pivotal element of the creation of state. Within nation-state realm, the members of society must positively demonstrate their contribution based on their respective capability. Al-FÃ¢rÃ¢bÃ® called, in addition, for the existence of freedom (al-á¸¥urriyah) for all people. The task of a state leader is to provide his members guidance to justly stride on right path in accordance with religious doctrines and to prevent them from going astray from the initial objective of state creation, i.e. triumphing happiness within the world and the hereafter. Al-FÃ¢rÃ¢bÃ®âs political thought has great influence in the next development of the modern democracy. The article indicates that al-FÃ¢rÃ¢bÃ®âs concept of freedom has been subsequently reinterpreted by the next Muslim scholars emphasizing that the concept of freedom he deemed is not a borderless freedom.